2015
DOI: 10.1017/s002531541500020x
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of the reproductive biology of albacore Thunnus alalunga from the western Mediterranean Sea

Abstract: Thunnus alalunga is an important commercial tuna species widely distributed in the three major oceans and the Mediterranean Sea. The Mediterranean population is currently classified as a data-poor stock and little is known about its basic life history parameters. This study provides the first detailed information on some aspects of the reproductive biology of T. alalunga from the western Mediterranean Sea. A total of 16 104 specimens were measured between 2005 and 2012. The overall sex ratio of females to male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
(67 reference statements)
2
6
1
Order By: Relevance
“…The minimum size-at-maturity found was 83 cm L F which is slightly smaller than that reported for North and South Pacific albacore (78–90 cm L F ; [23,24,32,52] and previous estimates for the Indian Ocean albacore (90 cm L F ; [59,60]), but larger than in the Mediterranean Sea (56 cm L F ; [26]). The present study is the first to calculate the L 50 for albacore tuna in the Indian Ocean based on histological analyses, with estimates of the L 50 at 85.3 ± 0.7 cm based on a vitellogenic 3 maturity threshold.…”
Section: Discussioncontrasting
confidence: 65%
“…The minimum size-at-maturity found was 83 cm L F which is slightly smaller than that reported for North and South Pacific albacore (78–90 cm L F ; [23,24,32,52] and previous estimates for the Indian Ocean albacore (90 cm L F ; [59,60]), but larger than in the Mediterranean Sea (56 cm L F ; [26]). The present study is the first to calculate the L 50 for albacore tuna in the Indian Ocean based on histological analyses, with estimates of the L 50 at 85.3 ± 0.7 cm based on a vitellogenic 3 maturity threshold.…”
Section: Discussioncontrasting
confidence: 65%
“…In the case of E. alletteratus in the southwest Gulf of Mexico, the population in global terms is in sex equilibrium (1:1), and the predominance of larger sized males is due to the fact that males reach greater lengths (Alcaráz-García, 2012). This finding is in agreement with other studies in tunids; for example, in albacore ( Thunnus alalunga ) fisheries in the western Mediterranean Sea, the number of females decreased for the greater sizes (Saber et al, 2015a).…”
Section: Discussionsupporting
confidence: 93%
“…Macroscopic examination of gonads and GSI values of albacore from the western Mediterranean indicated that fish were able to spawn. The estimated high GSI values were similar to values observed in the same area (Saber et al, 2015), and in the eastern Mediterranean Sea for males (Akayli et al, 2013) and females (Karakulak et al, 2016).…”
Section: Feeding Strategy and Trophic Levelsupporting
confidence: 86%
“…Our data showed that females dominated in the small length classes (between 60 and 70 cm SFL) while a greater abundance of males of larger length classes (above 80 cm FL) were found. The predominance of males in larger length classes has been reported in the Mediterranean albacore stock (Karakulak et al, 2011;Saber et al, 2015) as well as in the oceanic stocks (Ashida et al, 2020;Dhurmeea et al, 2016;Farley et al, 2013). The difference in sex ratio among length classes has been related to differences in natural mortality and vulnerability to capture (Schaefer, 2001;Schaefer et al, 2005) and by the growth difference due to the discrepancy in reproductive investment, which is higher in females than in males (Chen et al, 2012;Farley et al, 2013).…”
Section: Feeding Strategy and Trophic Levelmentioning
confidence: 83%
See 1 more Smart Citation